(untitled) (African Journal of Procurement, Logistics & Supply Chain Management, 2025)
The study examined the moderating effect of innovative capability on the relationship between transport cost minimization and performance and state-owned transport companies. The study exclusively relied on quantitative data analysis techniques. This study employed explanatory research design because explanatory research design is particularly valuable when there is a need to gain a deeper understanding of the relationships between variables. The results show that transport cost minimization has a significant positive effect on the performance of state-owned transport of the state-owned transport. Innovative capability significantly and positively impacts the performance of the state-owned transport. Innovative capability significantly enhances the performance of the state-owned transport company, it does not significantly moderate the relationship between transport cost minimization and performance of state-owned transport. The assess the influence of transport cost minimization on performance of state-owned transport companies. The study also examines the influence of innovative capability on performance of state-owned transport companies.